Epidemiological landscape of androgenetic alopecia in the US: An All of Us cross-sectional study - Aditya K. Gupta; Tong Wang; Vasiliki Economopoulos (PLoS ONE, 2025)
Background Androgenetic alopecia (AGA) is extremely prevalent with a multifactorial etiology. Materials We conducted a cross-sectional study using the All of US (AoU) dataset Sept 2024 to better understand the epidemiology, social determinants and management of AGA. Results Most males were 20–39 years old and females 60–69 years old. Men typically have an earlier onset of AGA than females. Male AGA is generally managed with finasteride; oral minoxidil is prescribed in younger males. Females are prescribed spironolactone and oral minoxidil with finasteride in post-menopausal females. There was very little dutasteride prescribed. Topical minoxidil is available over the counter and was not evaluated. Early in 2011 there were reports of the Post-Finasteride Syndrome (PFS); subsequently, the finasteride prescription rate fell to about 10–20% of the pre-PFS prescription rate. There was increased reporting for AGA in those who drink, have an annual household income ≥$75,000, and those with a higher level of education. There was also higher reporting of female AGA in those with anxiety and depression. Patients with higher income and education may have less pressing medical concerns enabling them to bring their AGA to the physician’s attention. Females in whom the AGA affects their anxiety and depression may seek help for the AGA as a way to address their underlying disorder. Conclusions This study provides a snapshot of the epidemiology and management of AGA in the USA. AGA is linked to the social determinants of health; addressing the AGA may help better manage the underlying mental and physical state.